Cardiopulmonary Exercise Test Interpretation Across the Lifespan in Congenital Heart Disease: A Scientific Statement From the American Heart Association - Barbara Cifra; Rachael L. Cordina; Naomi Gauthier; Laura C. Murphy; Tam Dan Pham; Gruschen R. Veldtman; Kendra Ward; David A. White; Stephen M. Paridon; Adam W. Powell (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Survivorship from congenital heart disease has improved rapidly secondary to advances in surgical and medical management. Because these patients are living longer, treatment and disease surveillance targets have shifted toward enhancing quality of life and functional status. Cardiopulmonary exercise testing is a valuable tool for assessing functional capacity, evaluating cardiac and pulmonary pathology, and providing guidance on prognosis and interventional recommendations. Despite the extensive evidence supporting the ability of cardiopulmonary exercise testing to quantitatively evaluate cardiovascular function, there remains confusion on how to properly interpret cardiopulmonary exercise testing in patients with congenital heart disease. The purpose of this statement is to provide a lifespan approach to the interpretation of cardiopulmonary exercise testing in patients with congenital heart disease. This is an updated report of the American Heart Association's previous publications on exercise in children. This evidence‐based update on the significance of cardiopulmonary exercise testing findings in pediatric, adolescent, and adult patients with various congenital cardiac pathologies and surgically modified physiology is formatted in a way to guide cardiopulmonary exercise testing interpretation practically for the clinicians and exercise physiologists who care for patients with congenital heart disease. Focus is placed on the indications for exercise testing, expected findings, and how exercise testing should guide the management of patients with various congenital heart disease subtypes. Areas for future intervention that could lead to improved care and outcomes for those with congenital heart disease are noted.